Legal Analysis of Divorce Due to Domestic Disputes and Quarrels in Religious Court Decision Number 1426/Pdt.G/2024/PA.Krs - Nasir, Muh; Aji, Aji (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Marriage is the implementation of the constitutional rights of every citizen guaranteed by Article 28B Paragraph (1) of the 1945 Constitution concerning the right to form a family and continue the lineage through a legal marriage. In addition, Article 28D Paragraph (1) affirms the right of every individual to obtain recognition, guarantees, protection, and fair legal certainty and equal treatment before the law. In this context, marriage is regulated by Law Number 1 of 1974 concerning Marriage which affirms that marriage aims to form a happy and eternal family based on the Almighty God. However, in practice, not all marriages run harmoniously and many end in divorce due to prolonged disputes and quarrels.This study aims to analyze the legal aspects of divorce due to disputes and quarrels in the household based on the Decision of the Religious Court Number 1426/Pdt.G/2024/PA.Krs. The research method used is normative juridical, with a statutory approach and analysis of court decisions to understand the legal basis, trial process, and judges' considerations in deciding divorce cases.The results of the study indicate that the divorce in this case was caused by household disharmony that continued since April 2016 until its peak in January 2017, which culminated in a divorce petition by the plaintiff. The court decided the divorce by granting iddah, mut'ah, and child support to the entitled party. This case emphasizes the importance of strengthening the mediation mechanism in the divorce process so that dispute resolution can be achieved peacefully before entering the court realm. Keywords: Dispute, Divorce, Quarrel.